The Relationship Between Laparoscopic Cystectomy and Ovarian Reserve: A Systematic Review and Meta-Analysis - Primarintan, Talita Nandia (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Laparoscopic cystectomy is the first-line recommended treatment for different ovarian cysts. Several mechanisms have been proposed to explain the negative impact of laparoscopic cystectomy on ovarian reserves, including the loss of normal ovarian tissue during cyst stripping, heat damage from electrosurgery, inflammation, and edema. The purpose of this systematic review is to synthesize and quantify the currently available research on the effect of laparoscopic cystectomy on ovarian reserve using multiple indicators. Material and Methods: The PubMed database was searched using the keywords